Effectiveness of Kenikir (Cosmos caudatus Kunth.) Leaf Extract on Duodenal Epithelial Damage of Aspirin Induced Male White Rats (Rattus norvegicus) - Siti Alfina; Husnarika Febriani; Syukriah Syukriah (Faculty of Medicine, University of Jember, 2022)
Aspirin or acetylsalicylic acid is one of the most common types of anti-inflammatory drugs used by people to relieve pain and inflammation. However, aspirin consumption can cause damage to the duodenal mucosal epithelium because it is acidic and inhibits the production of prostaglandins that are important in maintaining the mucosa. Duodenal damage due to aspirin consumption can be repaired using natural ingredients from plants with antioxidant and anti-ulcer effects, one of which is kenikir (Cosmos caudatus Kunth.) leaves. This study aims to determine the effectiveness of kenikir leaf extract against aspirin-induced histopathology and histomorphometry of the duodenum of male white rats. The research design used a completely randomized design (CRD) with 5 treatments and 5 replications. The treatments consisted of a normal group (feed and drink ad libitum), an aspirin group (induction of aspirin 200 mg/kgBW), and a treatment group with kenikir leaf extract at a dose of 700 mg/kgBW, 800 mg/kgBW, and 900 mg/kgBW. Preparation of histopathological preparations of the duodenum used the paraffin method with Hematoxylin-Eosin staining. Data were analyzed using one-way ANOVA and Duncan's follow-up test. The results of the histopathology study showed a significant difference (p<0.05) on the integrity score of duodenal mucosal epithelial cells. Histomorphometry had a significant effect on the height villi, basal width, apical width, and villous area (p<0.05). It can be concluded that administration of kenikir leaf extract at a dose of 900 mg/kgBW was most effective in improving the histopathology and duodenal histomorphometry of aspirin-induced male white rats. Keywords: aspirin, duodenum, kenikir (Cosmos caudatus Kunth.)